Pengaruh kecerdasan kinestetik dalam meningkatkan kreativitas koreografi instruktur aerobik - Riyadi, Slamet; Sabarini, Sri Santoso; Liskustyowati, Hanik; Yuzela, Anita (Universitas Nusantara PGRI Kediri, 2023)
This study aimed to determine how crucial kinesthetic intelligence is in adding to the choreographic creativity of callisthenics preceptors. This exploration system was carried out by experimental exploration styles using quantitative approaches. Purposive sampling was used as a sampling technique. The subjects of this research were 40 licensed aerobics instructors. Data analysis Techniques used Quantitative Analysis Techniques. The instrument used was the TTCT-Verbal Test (Torrance Test of Creative Thinking-Verbal) from Joy Paul Guilford. Data analysis using SPSS statistical software with the Two Way ANOVA Test. The results of this research stated that instructors with high kinesthetic intelligence exhibited no significant effect on choreographic creativity (Sig. 0.961 > 0.05). However, instructors with low kinesthetic intelligence showed an increase in choreographic creativity (Sig. 0.036 < 0.05). The final results showed that low and high levels of kinesthetic intelligence have no influence on choreographic creativity (Sig. 369 > 0.05). These unexpected results challenge existing understanding, offering a new perspective that kinesthetic intelligence is not a crucial thing that can influence choreographic creativity in aerobics teaching. Consequently, the study advises aerobics instructors to enhance their choreography creativity, emphasizing the need to consider not only appropriate training methods but also the physical components conducive to success.